Strategi Penerapan Teknologi Pembelajaran Berbasis Web Untuk Meningkatkan Minat Belajar Siswa Sekolah Menengah Pertama - Nofi Qurniati; Yoli Andi Rozzi; Siti Sundari; Achmad Fikri Sallaby; Khairien Eka Putri (Universitas Dehasen Bengkulu, 2024)
The development of information technology provides significant opportunities to improve the quality of learning in schools. One of the uses of this technology is the implementation of web-based learning technology. This community service activity aims to increase the learning interest of junior high school students through the application of web-based learning technology at SMP Negeri 11 Bengkulu Tengah. The methods used in this activity include the preparation stage, the implementation of socialization and training, and the evaluation stage. The activity was carried out by providing students with an understanding of the use of web-based learning media and direct practice in using digital learning platforms. The results of the activity indicate that the use of web-based learning technology can increase students' interest and participation in the learning process. In addition, students become more active in accessing learning materials independently. Therefore, the implementation of web-based learning technology can be an effective strategy to improve students' learning interest at the junior high school level.